PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK-PAIR-SHARE TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS VII SMPN 6 PARIAMAN TAHUN PELAJARAN 2013/2014 - Alimah, Bainil Ana (Pendidikan Biologi, 2014)
The background of this study is the studentsâ less study result in history social knowledge at grade VII of SMPN 6 Pariaman. The studentsâ less study result is caused by some factors, one of them is the history learning is still centered on the teacher. Students just hear and notice, they are not too motivated in learning history. The teacher totally uses speech model so that they are not active in the learning. One way to solve the problem is by using cooperatif learning model type think-pair-share. This study type is experimental research and this study design is Randomized Control Group Posttest Only Design. The population of this research is all class VII grade student of SMPN 6 Pariaman academic year 2013/2014. The taken sample is done with purposive sampling , so it is chosen for VII 1 grade ( experiment class) and VII 2 ( controlled class). The data of this research is the result of student learning which overhelms cognitive competence only. Based on the last test, it can be concluded that cooperative learning model type think-pair-share can improve the learning result of biology toward VII grade students in SMPN 6 Pariaman.